A NOTE ON THE TRIPARTITE RAMSEY NUMBERS \(r_t\)(\(C_4;2)\) AND \(r_t\)(\(C_4;3)\) - Buada, S.; Samana, D.; Longani, V. (Italian Journal of Pure and Applied Mathematics, 2015)
The k-colored tripartite Ramsey numbers rt(G;k) is the smallest positive integer n such that any k-coloring of lines of a complete tripartite graph Kn,n,n there always exists a monochromatic subgraph isomorphic to G. The values of rt(C4;2) = 3, and rt(C4;3) = 7 are discussed in the article The tripartite Ramsey numbers rt(C4;2) and rt(C4;3) of the Italian Journal of Pure and Applied Mathematics, n. 33-2014. However, there are our technical mistakes on three figures of the article. In this note we correct these mistakes.